Histological examination of explanted tissue-engineered bovine pericardium following heart valve repair. (12th October 2019) - Deutsch, Oliver; Bruehl, Frido; Cleuziou, Julie; Prinzing, Anatol; Schlitter, Anna Melissa; Krane, Markus; Lange, Rüdiger
Abstract: OBJECTIVES: Our goal was to present histopathological findings of human explants of a tissue-engineered bovine pericardium CardioCel (Admedus Regen Pty Ltd, Malaga, WA, Australia) used for heart valve repair in patients with congenital and acquired heart valve disease. METHODS: Sixty patients underwent heart valve repair from May 2014 to November 2018 using CardioCel as a substitute for valve tissue. We identified 9 cases in which the CardioCel patch was explanted following valve repair and available for histomorphological analyses. CardioCel explants were evaluated histologically using haematoxylin and oeosin, Elastica van Gieson and immunohistochemical stains. RESULTS: The indications for explantation were related to the CardioCel patch in 6 patients. Median time between the implantation and explantation was 242 (range 3–1247) days. We demonstrated a characteristic remodelling pattern with superficial coating of the tissue-engineered bovine pericardium by granulation tissue composed of histiocytes, few lymphocytes and fibrin. We had 2 cases with a multifocal nodular disruption, fragmentation and sclerosis of the decellularized collagen matrix with focal calcification after 795 and 1247 days in situ . CONCLUSIONS: Our data suggest that the tissue-engineered CardioCel patch is initially tolerated in the valvular position in the majority of patients. However, we also experienced graft failures that showed degeneration with fragmentation of the collagen matrix and even 2 cases with focal calcification evident from the histopathological analysis. Further analyses of mid- and long-term performance are mandatory.